Child Undernutrition in Pakistan : What Do We Know? - Raju, Dhushyanth (World Bank, Washington, DC, 2017)
Pakistan has an extraordinarily high and persistent level of child undernutrition. To effectively tackle the problem, the design of public policies and programs needs to be based on evidence. Toward this end, this paper presents a narrative review of the available empirical and qualitative literature on child undernutrition in Pakistan. It summarizes evidence for the country on, among other things, food consumption, spatial variation and trends in undernutrition rates, levels and effects of generally theorized determinants of undernutrition, and effects of various interventions on undernutrition. Based on patterns revealed in and insights gained from the cumulative evidence, the review lays out considerations and suggestions for further data collection and research, and for policy and practice.